Answer:
J' = (3,12)
K' = (18,12)
L' = (18,3)
M' = (3,3)
Explanation:
To apply the mapping rule, replace the x and y in the rule with the original coordinates.
The x coordinate of J is 1, applying the mapping rule, the x coordinate of J' will be 3x1 = 3
The y coordinate of J is 4, applying the mapping rule, the y coordinate of J' will be 3x4 = 12
So the coordinates of J' will be (3,12)
The x coordinate of K is 6, applying the mapping rule, the x coordinate of K' will be 3x6 = 18
The y coordinate of K is 4, applying the mapping rule, the y coordinate of K' will be 3x4 = 12
So the coordinates of K' will be (18,12)
The x coordinate of L is 6, applying the mapping rule, the x coordinate of L' will be 6x3 = 18
The y coordinate of L is 1, applying the mapping rule, the y coordinate of L' is 3x1= 3
So the coordinates of L' will be (18,3)
The x coordinate of M is 1, applying the mapping rule, the x coordinate will be 3x1 = 3
The y coordinate of M is 1, applying the mapping rule, the y coordinate will be 3x1 = 3.